2017
DOI: 10.20937/rica.2017.33.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Búsqueda De Capacidad Productora De Biosurfactantes en Actinobacterias Haloalcalófilas Y Haloalcalotolerantes

Abstract: Palabras clave: bacteria, emulsificante, tensoactivo, contaminación, biorremediación RESUMENUna opción para biorremediar ambientes salinos contaminados con compuestos orgá-nicos hidrofóbicos, es el uso de microorganismos haloalcalófilos o haloalcalotolerantes capaces de producir biosurfactantes estables y consumir al compuesto hidrófobo. El biosurfactante solubiliza al contaminante haciéndolo biodisponible para el microrganismo. De estudios previos se conocía la capacidad de siete actinobacterias haloalcalotol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Within the methodologies used to detect the production capacity of biosurfactants in the bacterial supernatant, the more sensitive described in the literature were the drop collapsing and oil displacement. In the case of hemolytic activity, not all biosurfactants have this activity, for this reason, we used it as a complementary test [ 49 , 50 ]. In our study, supernatants of My-30, S-69 and S-74 showed, indeed, a different degree of ability to produce biosurfactants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the methodologies used to detect the production capacity of biosurfactants in the bacterial supernatant, the more sensitive described in the literature were the drop collapsing and oil displacement. In the case of hemolytic activity, not all biosurfactants have this activity, for this reason, we used it as a complementary test [ 49 , 50 ]. In our study, supernatants of My-30, S-69 and S-74 showed, indeed, a different degree of ability to produce biosurfactants.…”
Section: Discussionmentioning
confidence: 99%
“…After 48 h at 35° C incubation, the plates were examined for colony growth with a zone of clearance around the colony. The biosurfactants had the ability to induce lysis of the blood erythrocytes [ 27 , 50 ].…”
Section: Methodsmentioning
confidence: 99%